2016
DOI: 10.1007/s11367-015-1021-5
|View full text |Cite
|
Sign up to set email alerts
|

Lead industry life cycle studies: environmental impact and life cycle assessment of lead battery and architectural sheet production

Abstract: Purpose This paper will give an overview of LCA studies on lead metal production and use recently conducted by the International Lead Association. Methods The lead industry, through the International Lead Association (ILA), has recently completed three life cycle studies to assess the environmental impact of lead metal production and two of the products that make up approximately 90 % of the end uses of lead, namely lead-based batteries and architectural lead sheet. Results and discussion Lead is one of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 3 publications
0
30
0
Order By: Relevance
“…Lead and lead-containing compounds have been used for millennia, initially for plumbing and cookware [ 1 ], but now find application across a wide range of industries and technologies [ 2 ]. Figure 1 a shows the global quantities of lead used across a number of applications including lead-acid batteries (LABs), cable sheathing, rolled and extruded products, ammunition, alloys, pigments and gasoline additives during the latter part of the twentieth and beginning of the twenty-first centuries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lead and lead-containing compounds have been used for millennia, initially for plumbing and cookware [ 1 ], but now find application across a wide range of industries and technologies [ 2 ]. Figure 1 a shows the global quantities of lead used across a number of applications including lead-acid batteries (LABs), cable sheathing, rolled and extruded products, ammunition, alloys, pigments and gasoline additives during the latter part of the twentieth and beginning of the twenty-first centuries.…”
Section: Introductionmentioning
confidence: 99%
“…A general trend of decreasing lead use occurred for most applications since the 1980s with the exception of LABs. The consumption of lead through the production of LABs increased from 0.6 Mt of lead in 1960 to 10 Mt in 2012, when it accounted for greater than 85% of lead used [ 2 ]. This increase was due to two factors, the increased number of automotive vehicles and so-called ‘deep cycle’ LABs which are popular for standby and emergency power supply, with automotive LABs accounting for 75% and deep cycle LABs 25% of the sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu undertook a LCA method for LABs used in e-bikes by accounting for twelve environmental impact categories and claimed that 95% of total lead emissions were released at the end-of-life stage [9]. According to the study of Davidson, lead production is the dominant contributor to environmental impacts in LABs and lead sheet [28]. Zhang also evaluated the life cycle environmental impacts of LABs in terms of global warming, acidification and respiratory effect, which showed that the proportion of lead in the LABs was 73.26% of the total mass and the environmental burdens were mainly caused by the consumption of lead resources [3].…”
Section: Introductionmentioning
confidence: 99%
“…The authors point out the importance of the lead-acid batteries recycling which can lessen the environmental impact by 50%. Alistair et al [12] carried out an LCA analysis among the others for lead-acid batteries. It was found that the manufacture and production stages do not play a dominant role in the environmental impact.…”
Section: Introductionmentioning
confidence: 99%